A CDPK isoform participates in the regulation of nodule number in Medicago truncatula - Gargantini, Pablo Ruben (2006)
Medicago spp. are able to develop root nodules via symbiotic interaction with Sinorhizobium meliloti. Calcium-dependent protein kinases (CDPKs) are involved in various signalling pathways in plants, and we found that expression of MtCPK3, a CDPK isoform present in roots of the model legume Medicago truncatula, is regulated during the nodulation process. Early inductions were detected 15 min and 3-4 days post-inoculation (dpi). The very early induction of CPK3 messengers was also present in inoculated M. truncatuladmi mutants and in wild-type roots subjected to salt stress, indicating that this rapid response is probably stress-related. In contrast, the later response was concomitant with cortical cell division and the formation of nodule primordia, and was not observed in wild-type roots inoculated with nod- strains. This late induction correlated with a change in the subcellular distribution of CDPK activities. Accordingly, an anti-MtCPK3 antibody detected two bands in soluble root extracts and one in the particulate fraction. CPK3::GFP fusions are targeted to the plasma membrane in epidermal onion cells, a localization that depends on myristoylation and palmitoylation sites of the protein, suggesting a dual subcellular localization. MtCPK3 mRNA and protein were also up-regulated by cytokinin treatment, a hormone linked to the regulation of cortical cell division and other nodulation-related responses. An RNAi-CDPK construction was used to silence CPK3 in Agrobacterium rhizogenes-transformed roots. Although no major phenotype was detected in these roots, when infected with rhizobia, the total number of nodules was, on average, twofold higher than in controls. This correlates with the lack of MtCPK3 induction in the inoculated super-nodulator sunn mutant. Our results suggest that CPK3 participates in the regulation of the symbiotic interaction.